Sustainable Informatics and Engineering harmonizing human & natural ecosystem : technical programme & abstracts (Institute of Technology Petronas Sdn.Bhd, Universiti Teknologi Petronas, 2010)
The aim of this symposium is to provide an excellent platform for professionals, engineers, academicians and practitioners worldwide to share and exchange research knowledge and ideas in technologies and applications in the field of Information and Communication Technology (ICT)